Female sika deer have evolved larger incisors than males under relaxed selection against rapid tooth wear. (21st June 2013) - Kubo, Mugino O.; Minami, Masato; Higuchi, Naoko; Ohnishi, Nobumasa; Okada, Ayumi; Kaji, Koichi; Ohba, Takahiro; Hosoi, Eiji; Koizumi, Toru; Takatsuki, Seiki
Abstract : Incisor size is associated with feeding efficiency in herbivorous ungulates and may have been under selection in correspondence with food habits. In the meantime, males of polygynous, dimorphic species have smaller cheek teeth than females, possibly because their reproductive span is much shorter than that of females. Thus, males are not under selection for more durable teeth when there is no reproductive return. Therefore, incisor size is expected to be under natural selection against wear and under the influence of sex‐based differences in reproductive strategy. We first investigated incisor wear in Japanese sika deer ( Cervus nippon ) and compared wear rates between the sexes and two ecologically contrasting populations on Kinkazan Island and Mt. Goyo. We then compared unworn incisor size to test the hypotheses that female deer have relatively larger incisors than males and a population with faster incisor wear has larger incisors. The Kinkazan deer showed significantly faster wear than those on Mt. Goyo, and Kinkazan males had faster wear than Kinkazan females. Unworn incisor size was relatively larger for females than that for males and was larger for Kinkazan deer than that for Mt. Goyo deer. The sex‐based difference in incisor size was greater in Mt. Goyo deer than that in Kinkazan deer. These findings support the hypothesis that sex‐based differences in reproductive span result in larger incisor size for female sika deer and imply that strong natural selection against rapid tooth wear diminishes sex‐based differences in incisor size in Kinkazan deer. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 384–397.